Factors Associated with Substance Use in Adolescents Under Legally Required Health Care - Kardaş, Ömer; Gümüşsoy, Ahmet Sefa; Benk Ayaz, Ayşe Merve; Kardaş, Burcu; Çimen, İrem Damla (The Bulletin of Legal Medicine, 2023)
Objective: Cases who applied to the polyclinic, where we followed the patients under legally required health care clinic in the last year, were evaluated. It was aimed to compare the socio-demographic and clinical characteristics of patients who use and do not use substances.Methods: The files of cases aged 14-18 years with health precautions were reviewed retrospectively. Results: Thirty four patients (21 girls, 13 boys) had substance use. The mean age was 15.9±1.2 years and the mean duration of education was 9.5±1.9 years. Legally required counseling was 72% (n=54), education was 29.3% (n=22), institutional care was 22.7% (n=17) Smoking and alcohol use (p=0.001) school absenteeism (p=0.002), criminal behaviour (p=0.012), number of negative life events (p=0.025), exposure to emotional abuse (p=0.025) and care measures (p=0.017) were found to be higher in patients with substance use. Academic achievement was lower in patients using substance (p=0.001). At least one psychiatric diagnosis (p=0.001), more than one psychiatric diagnosis (p=0.001) and conduct disorder (p=0.016) were detected more frequently in the substance abuser group. Cannabis was the most frequently used substance (79.4%) in the group using drugs.Conclusion: Adolescents who are monitored with in the scope of under legally required health care and who use substances are different from the non-substance use group in terms of some socio-demographic and clinical characteristics. Knowing these features can contribute to the prevention and treatment studies of forensic medicine and child and adolescent mental health clinics working with patients who receive legally required treatment.
Keywords: Adolescence; Addiction; Substance use; Legally Required Health Care; Neglect; Abuse